COMBINATION EFFECT AMONG GIVING TRIPOD POSITION AND PURSED LIP BREATHING TO RESPIRATION RATE IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) PATIENTS - Emyk Windartik; Eka Nur Soemah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
The purpose of this study was to analyze the effect of a combination of tripod position and pursed lip breathing on respiration rate in COPD patients at Bangil Hospital. In this study, a pre-experimental method was used to determine the effect of giving a combination of tripod position and pursed lip breathing on respiration rate in COPD patients at Bangil Hospital, Pasuruan. The population in this study were all COPD patients at Bangil Hospital Pasuruan in June 2021 as many as 30 people. The sampling technique in this study was consecutive sampling. The sample used in this study were some COPD patients at Bangil Hospital, Pasuruan. From the results of the research above, there are differences in the decrease in respiration rate , this can be caused by differences in the accuracy of respondents when doing pursed lip breathing , respondents who can do it correctly will get better results in reducing respiration rate . It can be concluded that there is an effect of giving a combination of tripod position and pursed lip breathing on respiration rate in COPD patients at Bangil Hospital, Pasuruan.